Experimental animal model for mucopolysaccharidosis: suramin-induced glycosaminoglycan and sphingolipid accumulation in the rat. - Constantopoulos, G (1980)
Intracerebral injection of the trypanocidal drug suramin in rats caused the formation of membranous neuronal and neuroglial inclusions. Here we show that intravenous administration suramin, 500 mg/kg, to 2-month-old rats causes a 5- to 8-fold increase of glycosaminoglycan concentration in the liver within 10 days and a 6-fold increase in urinary glycosaminoglycan excertion. The excess glycosaminoglycans consist of heparan sulfate and dermatan sulfate. Intracerebral injection of 250 micrograms of suramin results in a small increase of glycosaminoglycan and larger increase of ganglioside GM2, GM3, and GD3 concentrations in the treated region of the brain. The activities of the lysosomal enzymes iduronate sulfatase, beta-glucuronidase, and hyaluronidase in the liver of the suramin-treated mature rats were consistently decreased, whereas those of alpha-L-iduronidase, heparan N-sulfatase, arylsulfatase B, and others were considerably increased. The activity of iduronate sulfatase was completely inhibited in vitro by suramin at concentrations of 50 microM or higher. The activity of beta-glucuronidase was also strongly inhibited by low concentrations of suramin, but this inhibition was partially decreased at higher concentrations of the drug. The inhibition of both enzymes by suramin was noncompetitive. The suramin-treated rat may be a useful experimental animal model of mucopolysaccharidosis.